2003
DOI: 10.1029/2002jd002499
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment of global gridded precipitation for systematic bias

Abstract: [1] Systematic biases in gauge-based measurement of precipitation can be substantial. Of the sources of bias, wind-induced undercatch of solid precipitation is by far the largest. A methodology for producing gridded mean monthly catch ratios (CRs) for the adjustment of wind-induced undercatch and wetting losses is developed, which is suitable for application to continental or global gridded precipitation products. The adjustments for wind-induced solid precipitation were estimated using gauge type-specific reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
419
4
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(452 citation statements)
references
References 22 publications
15
419
4
3
Order By: Relevance
“…The most important systematic bias in Arctic precipitation measurements is a wind-induced undercatch of snow (Adam and Lettenmaier 2003;Rawlins et al 2009a). Correcting for this bias requires extensive data on wind speed, gauge type, and height of recording instruments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important systematic bias in Arctic precipitation measurements is a wind-induced undercatch of snow (Adam and Lettenmaier 2003;Rawlins et al 2009a). Correcting for this bias requires extensive data on wind speed, gauge type, and height of recording instruments.…”
Section: Discussionmentioning
confidence: 99%
“…Correcting for this bias requires extensive data on wind speed, gauge type, and height of recording instruments. Several attempts at bias correction for various time periods and regions have recently been performed (e.g., Yang and Ohata 2001;Adam and Lettenmaier 2003;Yang et al 2005), and these studies have generally indicated an underestimation of annual precipitation of about 10-25% over most of the pan-Arctic drainage, with higher values occurring in drainage basin parts that extend far north.…”
Section: Discussionmentioning
confidence: 99%
“…This may be an indication of an overestimate of topographic uplift at the 20-km grid spacing. On the other hand, observations over mountainous regions are often characterized by a low-elevation station bias and a gauge under-catch bias, which may account for an underestimate of true precipitation of up to 30% (Adam and Lettenmaier, 2003). This underestimate is maximum in winter, especially in the presence of blowing snow, and minimum in summer, thus showing a pronounced seasonality.…”
Section: Himed Simulationmentioning
confidence: 99%
“…This dataset was downscaled as described by Maurer et al (2009) using the bias-correction/spatial downscaling method (Wood et al, 2004) to a 0.5 degree grid, based on the 1950-1999 gridded observations of Adam and Lettenmaier (2003). The CMIP3 climate simulations datasets used in this study include the outputs of 16 IPCC Models under 3 future emissions scenarios (A2, A1B, B1,) resulting in a total of 48 different climate simulations containing monthly records of both precipitation and temperature at a 0.5 • spatial resolution for the period from 1950 until 2099.…”
Section: Climate Change Scenarios (Ccs)mentioning
confidence: 99%